1999
DOI: 10.1103/physrevb.59.7907
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo calculation of Compton profiles of solid lithium

Abstract: Recent high resolution Compton scattering experiments in lithium have shown significant discrepancies with conventional band theoretical results. We present a pseudopotential quantum Monte Carlo study of electron-electron and electron-ion correlation effects on the momentum distribution of lithium. We compute the correlation correction to the valence Compton profiles obtained within Kohn-Sham density functional theory in the local density approximation and determine that electronic correlation does not account… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 44 publications
(58 reference statements)
3
40
3
Order By: Relevance
“…[29][30][31][32][33][34] It is difficult to explain such a low value of Z k within the framework of the plasmaron-type physics underlying the conventional picture of the interacting electron gas. [35][36][37][38][39] We note, however, that the analysis of Compton data from a series of LiMg disordered alloys by Stutz et al 11 hinted that the behavior of Li may be idiosyncratic rather than being representative of metals more generally.…”
Section: ͑14͒mentioning
confidence: 77%
“…[29][30][31][32][33][34] It is difficult to explain such a low value of Z k within the framework of the plasmaron-type physics underlying the conventional picture of the interacting electron gas. [35][36][37][38][39] We note, however, that the analysis of Compton data from a series of LiMg disordered alloys by Stutz et al 11 hinted that the behavior of Li may be idiosyncratic rather than being representative of metals more generally.…”
Section: ͑14͒mentioning
confidence: 77%
“…In general, however, comparisons have shown that there are systematic anisotropic discrepancies between theory and experiment. As already noted, momentum densities have been calculated using the QMC methods [26,27] and the GW approximation [9,10,25]. However, in the case of Si [26], and Li [27] (QMC) and Li [38,25] (GW ) the correlation correction is not found to differ appreciably from the LP corrected LDA results [31].…”
Section: Compton Profilesmentioning
confidence: 99%
“…[48] have been calculated with the KKR band structure scheme and the LDA. The momentum density of Li has also been calculated using the LMTO method [17,18], the FLAPW method [9,10,11], the GW approximation [9,10,25], and quantum Monte Carlo methods [27]. Theoretical calculations based on the LDA have failed to describe the momentum density of Li also when the Lam-Platzman correlation correction has been taken into account [48].…”
Section: Bulk LImentioning
confidence: 99%
See 2 more Smart Citations